A Retrospective Long-Term Evaluation of Ununited Anconeal Process Excision on the Canine Elbow - Roy, R.G.; Wallace, L.J.; Johnston, G.R. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
A retrospective study was done to evaluate the long-term clinical radio-graphic effects of ununited anconeal process excision performed in dogs 5 to 12 months of age. Six dogs (seven surgically treated elbows) were evaluated at a mean of 65 months postoperatively for front limb lameness, elbow range of motion, and radiographic evidence of osteoarthritis. Limb use was considered good to excellent in 6 of 7 dogs. Osteo-arthritis, which progressed in all surgically treated elbows, was considered severe in three, moderate in one and mild to moderate in three. Early excision of an ununited anconeal process results in progressive osteoarthritis and a mild decrease in range of motion but good long-term function of the canine elbow joint.Long-term evaluation of dogs with excision of an ununited anconeal process was performed. Long-term limb use was considered good to excellent in six of seven dogs. Early excision of an ununited anconeal process results in progressive osteoarthritis and a mild decrease in range of motion but good long-term function of the canine elbow joint.
Keywords: Elbow; anconeus; ununited anconeal process; arthritis; juvenile bone disease